Implementation of the policy of cotton monopoly in the Surkhandarya oasis in 1946-1970 and its consequences - Yaqubova Diloram Tadjievna (Peerian Journals Publishing, 2022)
In the post-World War II years, Uzbekistan began construction of large irrigation facilities. This process was carried out in accordance with the orders of the Central Committee of the CPSU (b) and the Council of People's Commissars of the USSR issued in July 1945 and February 2, 1946. The period of construction of huge irrigation networks has begun in Surkhandarya region.
Keywords: Surkhan-Sherabad; Hazarbog; Tallimaron; South Surkhan Reservoir